(untitled) (International Journal of Innovative Technologies in Economy, 2018)
Any economic stress in itself carries a particular risk, since it creates problems in different areas, influencing individual incomes/expenditures, as well as incomes/ expenditures in the healthcare sector. The imbalance in the healthcare system can be understood as an unexpected phenomenon that occurs outside of the healthcare system but leads to negative consequences of access to resources in the healthcare system; in terms of access to medical services. The healthcare system in the Republic of Moldova is perceived as unproductive, which diminishes its prioritization. Therefore, the healthcare system is poorly funded, with few efficient regulations, which made it extremely sensitive during times of crisis, being unpredictable for new challenges. The authors consider that a method of anticipating the crisis in the healthcare system could be the application of economic and financial expertise.